Renovation of industrial building and its adaptation to the modern urban environment (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
Analysis of the features of the formation of urban public space through the renovation of industrial zones, as well as the identification of the prospects of this process and its impact on the existing structure of the city, based on existing domestic and foreign experience. Method. In modern conditions, with limited financial and material and technical resources of the state, the emergence of global and complex tasks of renovation of existing buildings is an expedient solution from the point of view of reducing costs for new construction. However, this is possible with the application of a comprehensive approach, which aims to preserve the originality, authenticity, identity and historical resources of the urban environment, and also allows to achieve a high predicted efficiency in the implementation of reconstruction projects in the shortest possible time. Renovation of industrial buildings refers to environmental praxeology - one of the content blocks of the theory of harmonization of the architectural environment, which investigates methods of effective organization of activities with the improvement of the artificially created environment.The results. As a result of the study, a comparative analysis of the domestic and foreign experience of renovation of industrial areas was carried out, and a number of factors affecting the renovation processes in the existing urban planning situation with the influence of all existing and possible processes were identified. It was found that depending on the tasks, different functional adaptation and direction of this or that industrial building or complex is possible, as well as its subsequent adaptation into the insuring system of the city.Scientific novelty. Different approaches to the process of renovation of industrial territories were identified and the principles of transforming the existing industrial function into a public space were substantiated.Practical significance. The analysis of the real state of industrial zones was carried out with the aim of an effective process of renovation of outdated and irrationally used industrial territory, which is located both in the structure of the city and outside it. All objects of renovation are considered in view of the time frame, the functional purpose of the buildings, the subject of the implementation of the investment project. Problems were studied and recommendations were made for the development of renovation in the capital and Ukraine in general, based on foreign experience and works.
Keywords: renovation; industrial zone; urban space; public space; urban planning situation; directions of renovation; modern approaches